(untitled) (Training and Practice : Journal of Educational Sciences, 2019)
The Teacher Training Center has been operating at the University of Pécs since 1 January 2015 to coordinate the work of the faculties of teacher training. It performs its tasks in network collaboration. The study presents the forms and scenes of these collaborations, especially with regard to practical training related to teacher training.